2009
DOI: 10.1111/j.1708-8305.2009.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk of Communicable Diseases aboard Cargo Ships

Abstract: Respiratory illness is the most common cause of presumably communicable diseases aboard cargo ships and may cause outbreaks of considerable morbidity. Although the validity of the data is limited due to the use of nonprofessional diagnoses, missing or illegible entries, and restriction of the study population to German ships, the results provide guidance to ship owners and to Port Health Authorities to allocate resources and build capacities under International Health Regulations 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In a study conducted by our institute the documented entries in 49 medical log books from seagoing cargo ships under the German flag between 2000 and 2008 were evaluated in order to assess the incidence rate of communicable diseases onboard. Nearly one fourth of the visits to the ships' infirmary were due to presumably communicable diseases with 75% of those being classified as acute respiratory diseases 36) .…”
Section: Communicable Diseasesmentioning
confidence: 99%
“…In a study conducted by our institute the documented entries in 49 medical log books from seagoing cargo ships under the German flag between 2000 and 2008 were evaluated in order to assess the incidence rate of communicable diseases onboard. Nearly one fourth of the visits to the ships' infirmary were due to presumably communicable diseases with 75% of those being classified as acute respiratory diseases 36) .…”
Section: Communicable Diseasesmentioning
confidence: 99%
“…In recent years, several studies have reported on mortality in passengers who have sailed in cruise ships and/or other types of passenger vessels [1,2]. Many other studies have reported on morbidity in cruise ship passengers, including injuries [3][4][5], various communicable diseases including gastroenteritis and influenza [3,[6][7][8][9][10], and acute cardiovascular diseases [11]. Little has been reported on mortality and its causes among crew members who serve on board cruise or passenger ships.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, however, this was only observed among the galley staff. According to the entries documented in 49 medical log books from seagoing cargo ships under German flag, nearly one fourth of the visits to the ship's infirmary were due to presumably communicable diseases, indicating the high relevance of infectious diseases in seafaring [24]. In cases of health problems aboard, seafarers can use the ship's infirmary and be treated by the ship's officer in charge of medical care.…”
Section: Discussionmentioning
confidence: 99%